Determining the effective slab width of composite joint with the weak-axis connection for ultimate bearing capacity. (April 2022) - Lu, Linfeng; Gao, Ming; Yan, Hongwei; Hao, Hanlin; Ding, Songlin; Liu, Yan
Abstract: Extensive brittle failures on the weld zone of beam bottom flange in composite joints of SMRFs were observed during the Northridge earthquake. One of the main reasons is the sizeable tensile strain demand generated at the beam bottom flange zone under sagging bending. The key to accurately understanding the mechanical properties of composite joints is the effective width of the slab. However, the previous research is all aimed at the I-section composited joints with column strong-axis connection or CFST column connection. Therefore, the research conclusions may not suit the composited joint with the weak-axis connection. Beam column weak axis connection is as universal as the strong axis connection. Therefore, this paper used ABAQUS software to investigate the effective width of the slab in composited joints with the weak-axis connection. Firstly, it defines the ultimate state of bearing capacity corresponding to the analysis in this paper. Secondly, it investigates the influence factor on the effective width of the slab under the ultimate sagging moment and hogging moment. Thirdly, it uses Gray Correlation Theory and MATLAB to fit the calculation formula of the effective width of the slab under the ultimate sagging moment and hogging moment. Fourthly, it compares the slab's effective flange width in the previous experiment and the formula presented in the paper. Finally, analyze the applicability of the fitting formula to the strong axis rigid composite joints and T-shaped rigid composite joints of the I-shaped column and H-beams.